Immigrants, evangelicals, and politics in an era of demographic change - Wong, Janelle (Russell Sage Foundation, 2018)
As immigration from Asia and Latin America reshapes the demographic composition of the U.S., some analysts have anticipated the decline of conservative white evangelicals' influence in politics. Yet Donald Trump captured a larger share of the white evangelical vote in the 2016 election than any candidate in the previous four presidential elections. Why has the political clout of white evangelicals persisted at a time of increased racial and ethnic diversity? In Immigrants, Evangelicals, and Politics in an Era of Demographic Change, political scientist Janelle Wong examines a new generation of Asian American and Latino evangelicals and offers an account of why demographic change has not contributed to a political realignment. Asian Americans and Latinos currently constitute more than one in every seven evangelicals, and their churches are among the largest, fastest growing organizations in their communities. While evangelical identity is associated with conservative politics, Wong draws from national surveys and interviews to show that non-White evangelicals express political attitudes that are significantly less conservative than those of their white counterparts. Black, Asian American, and Latino evangelicals are much more likely to support policies such as expanded immigration rights, increased taxation of the wealthy, and government interventions to slow climate change. As Wong argues, non-White evangelicals' experiences as members of racial or ethnic minority groups often lead them to adopt more progressive political views compared to their White counterparts. However, despite their growth in numbers, non-White evangelicals -- particularly Asian Americans and Latinos -- are concentrated outside of swing states, have lower levels of political participation than White evangelicals, and are less likely to be targeted by political campaigns. As a result, White evangelicals dominate the evangelical policy agenda and are overrepresented at the polls. Also, many White evangelicals have adopted even more conservative political views in response to rapid demographic change, perceiving, for example, that discrimination against Christians now rivals discrimination against racial and ethnic minorities. Wong demonstrates that immigrant evangelicals are neither "natural" Republicans nor "natural" Democrats. By examining the changing demographics of the evangelical movement, Immigrants, Evangelicals, and Politics in an Era of Demographic Change sheds light on an understudied constituency that has yet to find its political home. JANELLE S. WONG is professor of American Studies at the University of Maryland.